Metabolic Stress and Mitochondrial Dysfunction in Ataxia-Telangiectasia - Goutham Narayanan Subramanian; Abrey Jie Yeo; Magtouf Hnaidi Gatei; David John Coman; Martin Francis Lavin (MDPI AG, 2022)
The ataxia-telangiectasia mutated (ATM) protein kinase is, as the name implies, mutated in the human genetic disorder ataxia-telangiectasia (A-T). This protein has its "finger in many pies", being responsible for the phosphorylation of many thousands of proteins in different signaling pathways in its role in protecting the cell against a variety of different forms of stress that threaten to perturb cellular homeostasis. The classical role of ATM is the protection against DNA damage, but it is evident that it also plays a key role in maintaining cell homeostasis in the face of oxidative and other forms of non-DNA damaging stress. The presence of ATM is not only in the nucleus to cope with damage to DNA, but also in association with other organelles in the cytoplasm, which suggests a greater protective role. This review attempts to address this greater role of ATM in protecting the cell against both external and endogenous damage.